Surgeon-led improvement in compliance with use of sequential compression devices in a neurosurgery patient population - Sonora Andromeda Windermere; Daniel Sconzo; Asra Askari; Aristotelis Filippidis; Emanuela Binello (BMJ Open Quality, 2024)
Introduction Sequential compression devices (SCDs) are the mainstay of mechanical prophylaxis for venous thromboembolism in perioperative neurosurgical patients and are especially crucial when chemical prophylaxis is contraindicated.Objectives This study aimed to characterise and improve SCD compliance in neurosurgery stepdown patients.Methods SCD compliance in a neurosurgical stepdown unit was tracked across 13 months (August 2022–August 2023). When not properly functioning, the missing element was documented. Compliance was calculated daily in all patients with SCD orders, and then averaged monthly. Most common barriers to compliance were identified. With nursing, we implemented a best practice alert to facilitate nursing education at month 3 and tracked compliance over 9 months, with two breaks in surveillance. At month 12, we implemented a patient-engagement measure through creating and distributing a patient-directed infographic and tracked compliance over 2 months.Results Compliance averaged 19.7% (n=95) during August and 38.4% (n=131) in September. After implementing the best practice alert and supply chain upgrades, compliance improved to 48.8% (n=150) in October, 41.2% (n=104) in March and 45.9% (n=76) in April. The infographic improved compliance to 51.4% (n=70) in July and 55.1% (n=34) in August. Compliance was significantly increased from baseline in August to October (z=4.5838, p<0.00001), sustained through March (z=3.2774, p=0.00104) and further improved by August (z=3.9025, p=0.0001).Conclusion Beyond an initial Hawthorne effect, implementation of the best practice nursing alert facilitated sustained improvement in SCD compliance despite breaks in surveillance. SCD compliance nonetheless remained below 50% until implementation of patient-engagement measures which were dependent on physician involvement.